Hybrid procedures for aortic arch repair - Puślecki, Mateusz; Buczkowski, Piotr; Perek, Bartłomiej; Stachowiak, Wojciech; Misterski, Marcin; Juszkat, Robert; Kulesza, Jerzy; Żabicki, Bartosz; Stanisić, Michał Goran; Staniszewski, Ryszard; Ligowski, Marcin; Camacho, Estilita; et al. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Techniques of endovascular aortic repair (TEVAR) with stent grafts have become a method of choice in treatment of descending aortic diseases, particularly in patients in severe clinical status with concomitant disorders. Pathologies of the aortic arch as well as its branches require hybrid procedures. Open vascular operation (aortic arch debranching techniques) enable safe stent graft deployment. In this article we present our experience in the use of hybrid techniques, considering Landing Zones, in treatment of complicated aortic arch pathologies. Aortic diseases appear as an interdisciplinary problem that involve specialists in surgery, interventional radiology, anesthesiology and cardiology as well as employment of sophisticated medical equipment.